Pengaruh Metode Pembelajaran Interaktif Terhadap Motivasi Belajar Siswa Kelas II SDN 1 Kebaharan - Muhammad Faturohman; Desty Endrawati Subroto; Ghaisani Al - Amah; Ira Khoirunnisa; Siti Aisyah; Siti Alviyah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
The foundation of this study is the phenomenon of low learning motivation among students, which is manifested in their lack of active participation, minimal interest in what is learned, and weak enthusiasm for completing assignments. Teachers use conventional methods that do not actively involve students, which results in a lack of interest, enthusiasm, and participation in the teaching and learning process. Therefore, there is a need for innovation in learning. Participatory observation techniques were employed in this qualitative study. Data collection methods were carried out by closely observing the learning process. Consequently, it can be concluded that using interactive teaching techniques improves second-grade kids' motivation for learning. In order to establish an engaging learning environment and encourage kids to work more in class, this study suggests that primary school teachers use interactive approaches more often.